Pengaruh Brand Personality dan Sales Promotion terhadap Purchase Decision Produk Revlon (StudiPadaMahasiswiUniversitasBrawijaya) - OKTAVIANINGRUM, VENNTY AULIA (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study aims to determine the influence of brand personality and sales promotion of purchase decision Revlon cosmetic product. Type of research, conducted in this research is explanatory or explanatory research that is for theory or hypothesis, in order to find or change the theory or hypothesis research results already there is.The population in this research is the student of Brawijaya University who have bought or have used Revlon cosmetic product. In this research, the sampling technique is done by using non- probability sampling with purposive sampling technique. Data collection is done by distributing a questionnaire to Brawijaya University students. The sample in this research is 150 respondents. Data analysis techniques using SPSS for Windows ver 23.0.The result of the research shows that brand personality has significant influence to the variable of the decision of product purchase of Revlon and Sales Promotion variable does not influence to the decision of purchasing Revlon product.Variables among the studied are brand personality variables that affect the purchase decisions of Revlon products. With Revlon improves the quality of the brand personality and enhances sales promotion so as to attract consumers attention to make purchasing decisions.Keywords: Brand personality, Sales Promotion, Purchase Decision, Revlon